The Impact of Changes in Exchange Rates on Indicators of Stability in the Iraqi Economy after 2003 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study highlights the exchange rate policy as one of the important economic policies that support the work of the monetary and financial policy within the successful partial reforms. Those reforms are efficient and influential in economy structure, especially in the case of the availability of continuous structural reforms and control of unproductive expenditures with adopting many treatments that are devoid of defects and shortcomings in the economic, commercial and investment aspects. As well as, at the same time, it is considered a harmful policy if it is used in an economic environment that suffers from the most basic requirements of development due to the importance of most of the effects that the change in the exchange rate generates on the indicators of economic stability. However, what the Iraqi economy is experiencing in terms of the presence of a heavy legacy of inherent crises in the economy, perhaps the most important of which is the imbalance affecting the balance of payments, the general budget, the emergence of inflation and the rise in the public debt index is a clear translation of deep failures in the economic structure. Yet, the impact of the change in exchange rates is hardly devoid of a role in activating those failures that represent an obstacle to the progress of the economy through the negative effects that this change in exchange rates imposes on the reality of those indicators. Finally, this study has concluded that the weak and ineffective effect of adopting the policy of reducing the Iraqi dinar is due to the lack of complete adaptation in the structure of the Iraqi economy for the success of this implementation in the short term, with this reduction, Iraq has been distanced from economic stability, since the stability of any country is linked to the stability of the national currency exchange rate against foreign currencies, to ensure that it is far from the sharp fluctuations experienced by any country through the nature of the existing international and commercial relations with the countries of the world.